Comparing the Gene ACE Variant with Some Cardiac Muscle Variables for Handball Players - Nagham Salman Kareem (Journal of Global Pharma Technology, 2018)
The study objective to recognize the diversity of the gene ACE and the heart variables and the researcher used the descriptive research in the survey method to identify the majority of players who have cardiac functions that distinguish them from others according to genetic diversity where the dominant gene types were identified in the sample research (DD, ID , ii) The search sample was identified and chosen in the intentional manner, the 12-player handball players of the Diwaniya Governorate, divided by shapes into DD (6) players and (II) were (3) players and finally (ID) were (3) players and a blood withdrawal test was performed for the sample P Date on Monday (5 3 2018) and after which the checks were performed on the ACE gene and all the players have appeared to have the gene where the genes were dominant in the sample then the gene forms were detected to know the differences between groups through any group delayed to reach fatigue and the group. The gene structure (DD) is the most delayed to reach the anaerobic threshold where the researcher attributes that the genetic structure (DD) is what distinguished this group from others and the objectives of the search is to identify the types of the ACE as well as to identify the differences between the totals of the shapes according to the variables of the heart muscle In the fields of research, the human field was the handball players of the Diwaniya Sports and Spatial club, the sports hall in the Ramadan district and the period of time between (5 \03 2018) – (8 \05 2018) The statistical means were used (arithmetic mean, standard deviation, Variance test (p) for the differences between totals, the Law (LSD) is the least significant difference, Simple link.Keywords: ACE I, D gene and cardiac muscle.